Macrophage polarization markers in subcutaneous, pericardial, and epicardial adipose tissue are altered in patients with coronary heart disease - Papotti, Bianca; Opstad, Trine Baur; Åkra, Sissel; Tønnessen, Theis; Braathen, Bjørn; Hansen, Charlotte Holst; Arnesen, Harald; Solheim, Svein; Seljeflot, Ingebjørg; Ronda, Nicoletta (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND: Epicardial and pericardial adipose tissue (EAT and PAT) surround and protect the heart, with EAT directly sharing the microcirculation with the myocardium, possibly presenting a distinct macrophage phenotype that might affect the inflammatory environment in coronary heart disease (CHD). This study aims to investigate the expression of genes in different AT compartments driving the polarization of AT macrophages towards an anti-inflammatory (L-Galectin 9; CD206) or pro-inflammatory (NOS2) phenotype. METHODS: EAT, PAT and subcutaneous (SAT) biopsies were collected from 52 CHD patients undergoing coronary artery bypass grafting, and from 22 CTRLs undergoing aortic valve replacement. L-Galectin9 (L-Gal9), CD206 and NOS2 AT gene expression and circulating levels were analysed through RT-PCR and ELISA, respectively. RESULTS: L-Gal9, CD206 and NOS2 gene expression was similar in all AT compartments in CHD and CTRLs, as were also L-Gal9 and CD206 circulating levels, while NOS2 serum levels were higher in CHD (p=0.012 vs CTRLs). In CTRLs, NOS2 expression was lower in EAT vs SAT (p=0.007), while in CHD patients CD206 expression was lower in both SAT and EAT as compared to PAT (p=0.003, p=0.006, respectively), suggestive of a possible macrophage reprogramming towards a pro-inflammatory phenotype in EAT. In CHD patients, NOS2 expression in SAT correlated to that in PAT and EAT (p=0.007, both), CD206 expression correlated positively to L-Gal9 (p<0.001) only in EAT, and CD206 expression associated with that of macrophage identifying markers in all AT compartments (p<0.001, all). In CHD patients, subjects with LDL-C above 1.8 mmol/l showed significantly higher NOS2 expression in PAT and EAT as compared to subjects with LDL-C levels below (p<0.05), possibly reflecting increased cardiac AT pro-inflammatory activation. In SAT and PAT, CD206 expression associated with BMI in both CHD and CTRLs (p<0.05, all), and with L-Gal9 in EAT, however only in CTRLs (p=0.002). CONCLUSION: CHD seems to be accompanied by an altered cardiac, and especially epicardial AT macrophage polarization. This may represent an important pathophysiological mechanism and a promising field of therapy targeting the excessive AT inflammation, in need of further investigation.